외상후 스트레스장애 치료에 대한 한의학 임상연구 동향 - 주성준; Sungjun Joo; 권정은; Jungeun Kwon; 권찬영; Chan-young Kwon; 이보람; Boram Lee; 김상호; Sang-ho Kim (동의신경정신과학회지, 2019)
Objectives: The purpose of this study was to review the clinical research trends in the treatment of post traumatic stress disorder (PTSD) in Korean medicine (KM). Methods: We searched MEDLINE, CENTRAL, EMBASE, Google Scholar and five Korean databases through May 2019, for studies on KM to treat PTSD. Clinical research that conducted KM treatment of PTSD patients were included. Two researchers independently conducted study selection and data extraction process. Results: Totally, eight studies were included in this review. Types of traumatic events that patients experienced included physical violence/threatening, traffic accidents, sexual violence and personal tragic events. KM interventions performed included acupuncture, moxibustion, herbal medicine, physical therapy, and KM-based psychotherapy. Treatment duration varied from two days to more than five months. Follow-up began at least one week to three months after the end of treatments. It was reported that the major psychological and/or somatic symptoms of PTSD, such as anxiety, depression, insomnia, and musculoskeletal pain, subjectively improved, as well as other objective outcomes: Impact Event Scale-Revised Korean version (IES-R-K), Beck’s Depression Inventory (BDI), State-Trait Anxiety Inventory, Hwabyung Symptoms/characters, Electroencephalography (EEG) change, etc. Statistical studies were conducted in three studies only. Outcomes such as Visual Analogue Scale (VAS), BDI, and IES-R-K showed statistically significant improvement after KM treatments. There was no study reporting adverse events during or after the interventions. Conclusions: According to this review, diverse types of KM treatments have been used among PTSD patients in eight studies. The KM treatments effectively improved psychological and somatic symptoms of PTSD patients. However, the lack of high quality research as well as the lack of standardization of KM treatments for PTSD are limitations. Further methodologically robust clinical trials should be performed, and the standardization of KM treatments for PTSD should be sought.